Nonrigid Motion Correction With 3D Image‐Based Navigators for Coronary MR Angiography. Issue 5 (13th May 2016) - Luo, Jieying; Addy, Nii Okai; Ingle, R. Reeve; Baron, Corey A.; Cheng, Joseph Y.; Hu, Bob S.; Nishimura, Dwight G.
Abstract : Purpose: To develop a retrospective nonrigid motion‐correction method based on 3D image‐based navigators (iNAVs) for free‐breathing whole‐heart coronary magnetic resonance angiography (MRA). Methods: The proposed method detects global rigid‐body motion and localized nonrigid motion from 3D iNAVs and compensates them with an autofocusing algorithm. To model the global motion, 3D rotation and translation are estimated from the 3D iNAVs. Two sets of localized nonrigid motions are obtained from deformation fields between 3D iNAVs and reconstructed binned images, respectively. A bank of motion‐corrected images is generated and the final image is assembled pixel‐by‐pixel by selecting the best focused pixel from this bank. In vivo studies with six healthy volunteers were conducted to compare the performance of the proposed method with 3D translational motion correction and no correction. Results: In vivo studies showed that compared to no correction, 3D translational motion correction and the proposed method increased the vessel sharpness by 13% ± 13% and 19% ± 16%, respectively. Out of 90 vessel segments, 75 segments showed improvement with the proposed method compared to 3D translational correction. Conclusion: We have developed a nonrigid motion‐correction method based on 3D iNAVs and an autofocusing algorithm that improves the vessel sharpness of free‐breathing whole‐heart coronary MRA. Magn Reson Med 77:1884–1893, 2017. © 2016 International Society for Magnetic Resonance in Medicine